2023
DOI: 10.1039/d2ee03351h
|View full text |Cite
|
Sign up to set email alerts
|

Metastable-phase platinum oxide for clarifying the Pt–O active site for the hydrogen evolution reaction

Abstract: A new phase of 1T-phase platinum oxide exhibits a record acidic HER activity. A mechanism whereby the [Pt–O] active site can be easily attacked by protons to form the Pt–H intermediate state during the HER is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 43 publications
(43 reference statements)
2
48
0
Order By: Relevance
“…As a result, electrons tend to gather around O atoms, facilitating the absorption of H 2 O molecules on the O sites in a‐PtTe 2 NS. Subsequently, upon the dissociation of H 2 O molecules on a‐PtTe 2 NSs, the generated H * is adsorbed on the Pt sites that are close to the O sites to form a PtH configuration, [ 22 ] while OH * is bridged between the Pt and Te atoms (Figure S24, Supporting Information). The results mentioned above indicate that a‐PtTe 2 NSs can provide alternative active sites for the adsorption of H 2 O molecules due to oxygen heteroatom, delivering a promising opportunity to reduce the energy barrier for HER.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, electrons tend to gather around O atoms, facilitating the absorption of H 2 O molecules on the O sites in a‐PtTe 2 NS. Subsequently, upon the dissociation of H 2 O molecules on a‐PtTe 2 NSs, the generated H * is adsorbed on the Pt sites that are close to the O sites to form a PtH configuration, [ 22 ] while OH * is bridged between the Pt and Te atoms (Figure S24, Supporting Information). The results mentioned above indicate that a‐PtTe 2 NSs can provide alternative active sites for the adsorption of H 2 O molecules due to oxygen heteroatom, delivering a promising opportunity to reduce the energy barrier for HER.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Low dimensional metastable phase materials may have large specific surface areas with fully exposed the active sites and enhanced high atom utilizations. [18] Therefore the continuous development of these materials will create unlimited possibilities for performance innovation of catalytic reactions. Previous research has been demonstrated that combining mechanochemical and thermal treatment methods in a strong alkaline medium may produce materials with metastable phases as well as unique morphology.…”
Section: Introductionmentioning
confidence: 99%
“…21 In geometry, small-size nanoparticles usually expose more low-coordination sites and high surface areas, and thus they can increase considerably the chemical bond breaking in catalysis. The principle of size effect has been extensively used to express the activity enhancement of catalysts as a result of size decreasing, 4,17,[22][23][24] ranging from microscale-, nanoscale-, to cluster/single-atom catalysts. 5,9,16 Nevertheless, these small-sized catalysts only allowed smaller current densities in neutral electrolytes thus far (50-300 mA cm À2 ).…”
Section: Introductionmentioning
confidence: 99%